2016
DOI: 10.1149/2.0881606jes
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Kinetics of Protons and Oxide Ions in LSM/Lanthanum Tungstate Cathodes with Pt Nanoparticle Activation

Abstract: Composite electrodes of La 0.8 Sr 0.2 MnO 3 (LSM) / La 28-x W 4+x O 54+3x/2 (x=0.85, "LWO56") on LWO56 electrolytes have been characterized by use of electrochemical impedance spectroscopy vs pO 2 and temperature from 900 ⁰C, where LWO56 is mainly oxide ion conducting, to 450 ⁰C, where it is proton conducting in wet atmospheres. The impedance data are analyzed in a model which takes into account the simultaneous flow of oxide ions and protons across electrolyte and electrodes, allowing extraction of activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 24 publications
(45 reference statements)
1
12
0
Order By: Relevance
“…It should be again mentioned that the duration of each temperature step was equal to 3 h and impedance spectra were acquired every 30 min. Again, the dominant feature in the impedance spectra ( Figure 4 The charge transfer contribution compared to mass transfer processes is lowered at 850 o C, which could be attributed to the red-ox processes of intermediate reaction products (e.g., sulphur-containing species) or to the partial O 2transport of BZCY72 at high temperatures, as it has been observed in previous relevant works [18,19]. For this reason, the activation energy for Rct (29.7 kJ/mol) has been calculated taking into account the corresponding values in the temperature range of 700 -800 o C, thus excluding the point at 850 o C. (Fig.…”
Section: Effect Of Cell Temperaturesupporting
confidence: 68%
“…It should be again mentioned that the duration of each temperature step was equal to 3 h and impedance spectra were acquired every 30 min. Again, the dominant feature in the impedance spectra ( Figure 4 The charge transfer contribution compared to mass transfer processes is lowered at 850 o C, which could be attributed to the red-ox processes of intermediate reaction products (e.g., sulphur-containing species) or to the partial O 2transport of BZCY72 at high temperatures, as it has been observed in previous relevant works [18,19]. For this reason, the activation energy for Rct (29.7 kJ/mol) has been calculated taking into account the corresponding values in the temperature range of 700 -800 o C, thus excluding the point at 850 o C. (Fig.…”
Section: Effect Of Cell Temperaturesupporting
confidence: 68%
“…Adler et al [43] published a detailed study on the electrode kinetics of porous mixed-conducting oxygen electrodes based on oxide-ion conducting electrolyte, using a continuum modeling to analyze the oxygen reduction reaction. Furthermore, Strandbakke et al [44] showed that pre-exponential values of the Arrhenius plot are indicative of the microstructure impact in the electrochemical performance. A similar microstructure for both LaBaCo 2 O 5+δ and La 0.5 Ba 0.5 CoO 3−δ materials can be seen in Figure S1 and can also be confirmed with the similar pre-exponential values calculated from Figure 9 (13.55 for La 0.5 Ba 0.5 CoO 3−δ and 14.75 for LaBaCo 2 O 5+δ ).…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to lower the Co-content due to its high cost, the development of cathodes consisting of a mixture of 3d transition metals is investigated. Well-studied cathodes with Fe, Mn, or mixtures with Co have been reported in both single materials and composites [10,18,19]. Y-doped barium zirconate materials exhibit fast proton conduction and are state-of-the art electrolytes in PCFCs [1,20,21].…”
Section: Introductionmentioning
confidence: 99%